Beyond the lines : an autobiography - Nayar, Kuldip, 1923- (New Delhi : Roli Books ; Dhaka : Daily Star Books, 2012)
Autobiography of an Indian journalist, author, diplomat and parliamentarian.
Includes index.
Keywords: Nayar, Kuldip, -- 1923-; Journalists -- India -- Biography; India -- Politics and government -- 1947-